P228Association of vessel wall changes with cardiovascular risk markers in healthy individuals. (15th July 2014) - Ramanathan, R; Gram, J; Sidelmann, JJ; Bjerrum, IS; Diederichsen, ACP; Jespersen, J; Sand, NPR
Abstract: Objective: To characterize subclinical atherosclerosis in healthy, non-medicated middle-aged individuals and to compare these findings with classical cardiovascular risk factors and biochemical markers of inflammation and endothelial dysfunction. Methods: Participants were recruited from the Danish Risk Score Study. A total of 277 individuals, 66% of the invited, aged 50 or 60 years, without known cardiovascular disease or diabetes were randomly selected from national registries. Persons who did not take any medication represented the study population, N = 209. The population was separated in two groups according to coronary artery calcification (CAC) by non-enhanced cardiac-CT, and carotid plaque by ultrasound. Inflammation (C-reactive protein (CRP), fibrinogen and D-dimer) and endothelial dysfunction (von Willebrand factor, tissue-plasminogen activator (t-PA), and plasminogen activator inhibitor-1 (PAI-1)) were studied. Results: Coronary calcification was seen in 39 % while carotid plaque was observed in 28 % of individuals. Age, gender, smoking, blood pressure and triglycerides were significantly associated with CAC (P < 0.05), while age and smoking were significantly associated with carotid plaque (P < 0.005).The concentrations of t-PA and PAI-1 were significantly associated with CAC (P < 0.01), whereas fibrinogen levels were associated with plaque (P < 0.05). Logistic multivariate regression revealed that age, gender, systolic blood pressure and total cholesterol (P < 0.1) were associated with CAC, while no associations were found with carotid plaque. Conclusion: Even in apparantly healthy middle-aged individuals manifest morphological and biochemical signs of subclinical atherosclerosis were observed in more than 50 %. Markers of inflammation and endothelial dysfunction were associated with subclinical atherosclerosis in asymptomatic healthy individuals, but these changes seemed to be mediated through classical risk factors. Furthermore, we demonstrate that classical risk factors and biochemical markers are associated differently with atherosclerotic lesions depending on the vascular location.